Benefits of data aggregation on energy consumption in wireless sensor networks. Issue 8 (25th May 2017) - Lu, Yao; Kuonen, Pierre; Hirsbrunner, Beat; Lin, Mingwei
Abstract : Wireless sensor networks consist of a large number of distributed sensor devices, which are connected and coordinated through multi‐hop routing. Due to the existence of correlated information and redundancy in measuring data, data messages can be combined and merged by performing data aggregation function in the routing process. To reduce energy consumption is a major optimisation objective of data aggregation approaches, which can be achieved by decreasing the compulsory communication load of routing. From the theoretical level, an energy model is proposed to validate the benefits of data aggregation on energy consumption. The key parameters which may impact the aggregation performance are further discussed. Finally, the corresponding simulations are implemented in order to verify the analysis conclusions from the theoretical model, and the comparison results can effectively reflect the advantages of data aggregation in different scenarios.